Clindamycin/benzoyl peroxid gel in mild-to-moderate acne - Olga Yu. Olisova; Ekaterina M. Anpilogova (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
Acne is a widespread inflammatory disease affecting the pilosebaceous follicles of the skin. It mostly affects teenagers and, in most cases, clinical healing occurs as patients grow up. However, 1040% of adults may have acne tarda. Due to the fact that face is one of the favorite locations of rashes, acne significantly worsens the quality of life, as a result of which patients develop social phobia, anxiety disorders, depression and even suicidal ideas, which requires a personalized approach to prescribing highly effective treatment. According to world recommendations, regardless of the severity of acne, almost all patients are shown the use of local remedies. In our pharmaceutical market, the choice of this group of drugs is quite limited. However, in September 2022, a new drug appeared in the arsenal of Russian dermatologists, which is a combination of benzoyl peroxide and clindamycin. This review presents the accumulated experience of almost 20 years of foreign colleagues who have been successfully using a combination of benzoyl peroxide and clindamycin in the treatment of mild-to-moderate acne.